PRINCIPES DE BASE RELATIFS AU ROLE DES ARCHIVISTES ET DES GESTIONNAIRES DE DOCUMENTS POUR LA DEFENSE DES DROITS DE L’HOMME - HUman Rights Working Group International Council on Archives (Conseil International Des Archives, 2016)
Keywords: References - Comma (2020 1-2); Archives and Human Rights

Principios básicos sobre el papel de archiveros y gestores de documentos en la defensa de los derechos humanos: Documento de trabajo del Consejo Internacional de Archivos - HRWG ICA (Human Rights Working Group - International Council on Archives) (International Council on Archives, 2016)
Keywords: References - Comma (2020 1-2); Archives and Human Rights

ICA Human Rights Archives Directory - HRWG ICA (Human Rights Working Group - International Council on Archives) (Archivists Watch, 2011)
For some years now, the ICA Human Rights Working Group (HRWG) has been trying to establish a directory of human rights archives from around the globe. This summer, I began volunteering with the IC…
Keywords: References - Comma (2020 1-2); Archives and Human Rights